Γ-Ray-driven degradation of robust epoxy thermosets. Issue 5 (22nd March 2022) - Hu, Zhen; Xu, Ningdi; An, Ziqiang; Wang, Baolong; Lu, Fei; Tian, Bo; Yao, Gang; Liu, Yingying; Liu, Li; Huang, Yudong
Abstract : We exploit stable conjugated linkages, phenyl imine conjugated N–N bonds, for the γ-ray-induced controllable cleavage of polymer chains as a new methodology for the fabrication of γ-ray-degradable epoxy thermosets. Abstract : The γ ray is a promising candidate for thermoset material degradation owing to its high energy, strong penetrability, low carbon emission and economy. However, the development of irradiation degradation technology is limited by irradiation cross-linking and irradiation degradation simultaneously, and a controllable degradation remains a considerable challenge. Herein, we exploit stable conjugated linkages, phenyl imine conjugated N–N bonds, for the γ-ray-induced controllable cleavage of polymer chains. Using this distinctive conjugated structure, we design γ-ray-responsive epoxy networks that can be readily degraded at a dose of 40 kGy at room temperature and show mechanical properties, thermal properties and chemical resistance comparable to commodity epoxy resins. Additionally, the incorporation of a radical scavenger can reduce the uncontrolled recombination of degradation segments, which further accelerates the degradation of the epoxy thermosets.